Unfavorable microbiological impact of directly duodenal biliary drainage in patients with perihilar obstruction: a preliminary report - Rozhkova, Veronika; Tutuş, Kamuran; Kömeç, Selda; Kınacı, Erdem; Bostancı, Özgür; Özden, İlgin (Frontiers in Surgery, 2025)
BackgroundBiliary drainage is frequently used in patients with perihilar obstruction. This study was designed to compare the microbiological characteristics of patients whose biliary trees were either exposed or not exposed to duodenal fluid, depending on the drainage method used.MethodsThe charts of 71 patients with perihilar obstruction (any etiology causing an obstruction parallel to that of a proximal cholangiocarcinoma according to the Bismuth–Corlette classification) were evaluated retrospectively. The contacted group comprised 20 patients who underwent either endoscopic stenting or percutaneous transhepatic biliary drainage (PTBD) with duodenal extension, while the non-contacted group consisted of 51 patients with either external PTBD or surgery upfront.ResultsPositive bile culture results were identified in 19/20 (95%) vs. 17/51 (33%) patients (p = 0.00001) and multimicrobial growth in 13/19 (68%) vs. 4/17 (24%) (p = 0.007) patients in the contacted group and non-contacted group, respectively. Colonization of bile with multidrug-resistant (MDR) and extensively drug-resistant (XDR) bacteria was worse in the contacted group: 13/19 (68%) vs. 5/17 (29%) (p = 0.02). Significant differences were also found in the frequencies of carbapenem-resistant Enterobacterales (CRE) colonization: in the contacted group, positive CRE culture (p = 0.033) and PCR (p = 0.01) were more frequent.ConclusionsThe mode of the biliary drainage—duodenal vs. directly external—significantly modifies the microbiological characteristics of the patients with perihilar obstruction. Catheterization methods that entail continuous exposure of the biliary tree to duodenal fluid are associated with higher frequencies of bactibilia, presence of MDR and XDR bacteria in the bile, and intestinal colonization with CRE.